Pandangan Terhadap Pendidikan Seksual Pada Remaja: Literature Review - Suramto, Suramto; Bawono, Budhi; Suryanadi, Partono Nyana (Academy of Education Journal, 2024)
Sex education holds significant importance for teenagers from an early age due to their vulnerability to misinformation about sex. This dissertation aims to (1) explore teenagers' perceptions of sex education and (2) identify the sources they rely on for obtaining information about sex. Furthermore, sex education plays a crucial role in enlightening teenagers about various harmful sexual behaviors, enabling them to steer clear of such practices. The research employs a literature review methodology to unearth diverse information on adolescent sex education. Firstly, understanding adolescents' perception of sex education is deemed essential and advantageous in addressing their developmental challenges during this transitional phase from childhood to adulthood. Adolescence entails significant biological, cognitive, and socio-emotional changes, making sex education a pertinent tool to assist them. Secondly, teenagers predominantly turn to mass media, encompassing print media like newspapers, magazines, and books, as well as electronic media such as television and gadgets, for their sexual education. The mass media, along with peers, serves as the primary source of sexual information and knowledge for teenagers, as opposed to receiving such education from family or school environments.